2002
DOI: 10.1021/bi0262449
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Subunits D, E, and G in the Yeast V-ATPase Complex Using Cysteine-Mediated Cross-Linking to Subunit B

Abstract: Using a combination of cysteine mutagenesis and covalent cross-linking, we have identified subunits in close proximity to specific sites within subunit B of the vacuolar (H(+))-ATPase (V-ATPase) of yeast. Unique cysteine residues were introduced into subunit B by site-directed mutagenesis, and the resultant V-ATPase complexes were reacted with the bifunctional, photoactivatable maleimide reagent 4-(N-maleimido)benzophenone (MBP) followed by irradiation. Cross-linked products were identified by Western blot usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
105
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 57 publications
(106 reference statements)
4
105
0
Order By: Relevance
“…This shows that the interaction between subunits E and G is necessary to elongate subunit G in order for it to act as a stator. The positioning of the EG complex at the periphery of the V 0 -V 1 complex and its extended character are in accordance with cross-linking data of cysteine mutants that have shown that subunits E and G are in close contact to the outer surface of subunit-B of V 1 , reaching almost to the top of the V 0 -V 1 complex (19).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This shows that the interaction between subunits E and G is necessary to elongate subunit G in order for it to act as a stator. The positioning of the EG complex at the periphery of the V 0 -V 1 complex and its extended character are in accordance with cross-linking data of cysteine mutants that have shown that subunits E and G are in close contact to the outer surface of subunit-B of V 1 , reaching almost to the top of the V 0 -V 1 complex (19).…”
Section: Discussionsupporting
confidence: 88%
“…Based on the alignment of sequences of subunits G from several species, a region mapping to a single face of a predicted helix (26,43,44) has been proposed to be involved in protein-protein interaction. Cross-linking studies and native complex isolation also indicated that subunits E and G could form part of the peripheral stator (16,19). The data presented in this study clearly show that subunit E is a partner for subunit G. The fact that these subunits spontaneously associate after cleavage from their respective fusion partner and purify as a single entity when co-expressed is a clear indication of a tight and specific interaction.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The D subunit had been the most probable candidate of rotor subunit in V 1 portion (2). Cross-linking studies have suggested that the D subunit was adjacent to B subunit at central cavity region of A 3 B 3 hexamer, and the F subunit was associated with the D subunit (29,30). In contrast, studies on the V-ATPase from Manduca sexta suggested that subunit E, rather than subunit D, was the rotor subunit (31).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the other V 1 subunits is not so clear. It is thought that the central stalk may be composed of D (32 kDa) and F (14 kDa) subunits (8,9). The stator region is thought to be composed of E (27 kDa), G (13 kDa), C (42 kDa), and H (54 kDa) subunits (9 -13).…”
mentioning
confidence: 99%